Characterization and modelling of water mixing energies and particle behavior during wave generation in CanmetENERGY Devon spill test tank. (15th June 2023) - Liu, Ruixue; Daskiran, Cosan; Mukherjee, Abhishek; Xin, Qin; Cui, Fangda; Marras, Simone; Farooqi, Hena; Dettman, Heather; Boufadel, Michel
Abstract: A mesoscale oil spill test tank located in Natural Resources Canada research facility at CanmetENERGY Devon (AB, Canada) was used to study the mixing energy and particle behavior near the shorelines. Four types of waves have been generated in the tank where the instantaneous velocities were measured using an acoustic doppler velocimeter (ADV), and the energy dissipation rate was obtained. Below the water surface of 0.2 m, the energy dissipation rate reached the magnitude of 10 −4  W/kg slightly away from the tank beach and increased to 10 −3  W/kg in the beach region. For the most typical wave conditions, Large-Eddy Simulation (LES) were conducted and the result was consistent with experimental observation. The simulation further revealed that the energy dissipation rate reached 1.0 W/kg at the water surface near the beach region. The velocities and sub-grid diffusion from LES were used to track the movement of fictitious neutrally buoyant, buoyant, and heavy particles by a Lagrangian particle-tracking model. It was found that the droplet inertia has significant impact for 500 μm particles. Under the specific gravity of 0.88, the particles accumulated close to the beach, while the particles with specific gravity of 1.20 settled to the bottom wall regardless of the existence of waves. Highlights: The energy dissipation rate at surface reaches 0.1 to 1.0 w/kg when breaking at beach. The mixing energy is one order higher near the shoreline region. Particle/droplet size and inertia are important for predicting their transport.